Energy and economics: an empirical study on the global economic impact of energy crisis - Agrima Kumar RAJVANSHI; Sonali Ahuja DUA (Theoretical and Applied Economics, 2025)

(untitled)
This study aims to reveal the effects of extreme oil and gas price volatility during the energy crisis of 2022, examining the cause-effect relationship between energy crises and various economic factors. This paper questions not only the depth of the impact on an economic level but also its social implications by presenting empirical evidence while following an interdisciplinary approach. Series of regression analysis, Granger-Causality test with ADF stationarity and ACF models and multivariate correlation analysis were used. The results suggest that, increased cost of living, market volatility, change in supply patterns and policies are associated with extreme energy price fluctuations caused by various geopolitical factors and its large-scale impact due to globalization.